Current place of legumes on consumers’ plates in Benin and Burkina Faso ? - (:unkn) unknown (My University, 2025)
Only limited data are available on legume-based food consumption and potential impact of food transition on this consumption in West Africa. Hence, this study aimed to assess the current consumption of legumes-based food in Benin and Burkina Faso.Consumption has been measured among a sample of adult population using quantitative food frequency questionnaire in a cross-sectional survey. In Benin, in May 2023 and January 2024, 1476 individuals have been interviewed, split over urban and rural areas of 3 regions (South, Centre, North), in order to study the impact of agroecological conditions on legumes consumption. In Burkina Faso, because of the current security situation, the survey was carried out only in urban areas (Ouagadougou) among 991 individuals in September and December 2023.Cowpea, groundnut and African locust bean are the most frequently consumed species of legumes in both countries: respectively, 95 %, 94 % and 87 % of Beninese interviewees, and 88 %, 97 % and 96 % Burkinabe asked declared having consumed it within the month before the survey. Soybeans are eaten by a higher percentage of individuals in Benin than in Burkina Faso (84 % vs. 54 %). Bambara groundnut is consumed by almost 40 % of the population in both countries, meanwhile geocarpa groundnut is less consumed in Burkina Faso than in Benin (respectively 37 % and 3 %). Pigeon pea was identified only in Benin, and Zamnè (Acacia macrostachya) only in Burkina Faso. African locust bean is used only as condiment, unlike the other species that can be presented in a remarkable diversity of consumption forms : 64 foods listed in Benin and 48 in Burkina Faso. Respondents from both countries have consumed on average 4 different legumes in the week before the survey. Beninese consumed foods or condiments based on legumes 24 times, meanwhile in Burkina Faso, this weekly frequency was 13. In both countries, we noticed differences in consumption depending on gender and age of the individuals,
Keywords: African Research